2009
DOI: 10.1063/1.3267104
|View full text |Cite
|
Sign up to set email alerts
|

On the interface state density at In0.53Ga0.47As/oxide interfaces

Abstract: Articles you may be interested inBiaxially strained extremely-thin body In0.53Ga0.47As-on-insulator metal-oxide-semiconductor field-effect transistors on Si substrate and physical understanding on their electron mobility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 12 publications
6
97
0
Order By: Relevance
“…It has been reported for n-type In 0.53 Ga 0.47 As that the theoretical C-V response is asymmetrical in shape, with a reduction in accumulation capacitance expected on n-type due to both the fact that the density of states in the In 0.53 Ga 0.47 As conduction band ͑1.7 ϫ 10 17 cm −3 ͒ is over one order of magnitude lower compared to the In 0.53 Ga 0.47 As valence band ͑2.6ϫ 10 18 cm −3 ͒, and also due to charge quantization effects. 12,23, 24 Brammertz et al, 25 have reported that the inclusion of a large interface state distribution in the In 0.53 Ga 0.47 As conduction band leads to an increase in the modeled theoretical accumulation capacitance, due to the capacitance contribution from these interface states. This is in agreement with C-V responses typically measured on p-type and n-type In 0.53 Ga 0.47 As MOS structures which do not exhibit the asymmetry between the maximum accumulation capacitances.…”
Section: Temmentioning
confidence: 99%
“…It has been reported for n-type In 0.53 Ga 0.47 As that the theoretical C-V response is asymmetrical in shape, with a reduction in accumulation capacitance expected on n-type due to both the fact that the density of states in the In 0.53 Ga 0.47 As conduction band ͑1.7 ϫ 10 17 cm −3 ͒ is over one order of magnitude lower compared to the In 0.53 Ga 0.47 As valence band ͑2.6ϫ 10 18 cm −3 ͒, and also due to charge quantization effects. 12,23, 24 Brammertz et al, 25 have reported that the inclusion of a large interface state distribution in the In 0.53 Ga 0.47 As conduction band leads to an increase in the modeled theoretical accumulation capacitance, due to the capacitance contribution from these interface states. This is in agreement with C-V responses typically measured on p-type and n-type In 0.53 Ga 0.47 As MOS structures which do not exhibit the asymmetry between the maximum accumulation capacitances.…”
Section: Temmentioning
confidence: 99%
“…The simulation results of oxide/n-In 0.53 Ga 0.47 As MOSCAPs shows that the C-V curve of ideal device without any interface state density has an asymmetrical sharp with higher slope at negative voltage side and low minimum capacitance value, C min . 17 According to this result, in our case, the C-V characteristic of sample S3 indicates that this curve approach closest to the ideal curve as compared to either S1 or S2 ͑Fig. 4͒.…”
mentioning
confidence: 99%
“…By comparison, the evidence of high interface state density in sample S1 exhibited by the observation of highest value of C min as well as accumulation capacitance, C acc . 17 The conductance method with the application limited to the depletion region is used to estimate the interface trap density near midgap of sample S1 and sample S2. 18 From the Gp/ versus frequency curves shown in Figs.…”
mentioning
confidence: 99%
“…7 The observed dispersion is ascribed to the tunnelling of carriers into electrically active, near interface border traps in the oxide, [19][20][21] and fast interface states. 22,23 The larger frequency dispersion in the depletion region of the p-type MOSCAP also suggests a higher density of interface traps in the lower half of the bandgap. Following FGA, the frequency dispersion in accumulation and depletion is marginally improved for the p-type MOSCAP.…”
mentioning
confidence: 99%
“…Often C ox is deduced from the maximum accumulation capacitance, which is prone to error due to the effects of density of states and charge quantisation in the semiconductor 27 which is compounded by interface states and border traps. 14,22,23 An alternative is to calculate C ox based on the dielectric constant (k) and physical dielectric thickness obtained from transmission electron microscopy. This can also be erroneous given the uncertainty of the k-value of Al 2 O 3 , reported to be between 7 and 9 in literature, resulting in an assumed value of the dielectric constant to be used in the calculation.…”
mentioning
confidence: 99%